2018
DOI: 10.13075/ijomeh.1896.01183
|View full text |Cite
|
Sign up to set email alerts
|

Environmental non-persistent endocrine-disrupting chemicals exposure and reproductive hormones levels in adult men

Abstract: Non-persistent endocrine-disrupting chemicals (EDCs) are exogenous, man-made substances present in the environment that may interfere with the natural human hormones and may exert adverse consequences on human organism. Endocrinedisrupting chemicals have been suspected to be associated with altered reproductive function in the case of males and females. Environmental endocrine-disrupting non-persistent chemicals like parabens, phthalates, bisphenol A (BPA), synthetic pyrethroids and organophosphate pesticides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
(188 reference statements)
0
12
0
1
Order By: Relevance
“…Noninvasive markers are better suited to exclude NAFLD, rather than to diagnose NAFLD due to low sensitivity for detection of NAFLD in individuals with values >36. Based on current literature, the area under the receiver operating characteristic curve is 0.78‐0.84 representing modest accuracy . However, sensitivity analyses using different cut‐off demonstrated that our results were consistent and robust.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Noninvasive markers are better suited to exclude NAFLD, rather than to diagnose NAFLD due to low sensitivity for detection of NAFLD in individuals with values >36. Based on current literature, the area under the receiver operating characteristic curve is 0.78‐0.84 representing modest accuracy . However, sensitivity analyses using different cut‐off demonstrated that our results were consistent and robust.…”
Section: Discussionmentioning
confidence: 49%
“…However, sensitivity analyses using different cut‐off demonstrated that our results were consistent and robust. The USFLI and HSI have been established as robust noninvasive diagnostic modalities for NAFLD in the US population and other populations, and can reliably and independently predict liver‐related and all‐cause mortality . Future prospective studies are needed to reproduce and reconfirm these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the assessment of EDC exposure appears crucial in order to monitor populations at higher risk of exposure and to understand the link between exposure and adverse health effects. In biological samples concentrations of EDCs (e.g., bisphenol A (BPA), phthalates, parabens, polychlorinated biphenyls (PCBs), perfluorinated compounds, polybrominated diphenyl ethers) and metabolites of EDCs (e.g., metabolites of pyrethroids, insecticides, pesticides, phthalates) have been used as conventional biomarkers of exposure (Calsolaro et al 2017, Dziewirska et al 2018, Hampl et al 2016, Karwacka et al 2019). However, since 1995 (Sonnenschein et al 1995) some authors proposed novel biomarkers of exposure to EDCs, which focus on detecting the biological effect of chemical compounds or metabolites, rather than detecting the presence of the EDC itself.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive adverse effects of pesticides are related to sex. In men, pesticides exposure has been associated to reduced testosterone synthesis and sperm quality and motility, as well as testicular cancer; in women, the main effects were observed on the alteration of ovarian cycle, the imbalance of hormone concentrations and fertility, and the induction of spontaneous abortion [3,4].…”
Section: Introductionmentioning
confidence: 99%